A SYSTEM DYNAMICS APPROACH FOR STRATEGIC PLANNING OF CONSUMER ELECTRONICS INDUSTRY IN DEVELOPING COUNTRIES: THE CASE OF THE TELEVISION MANUFACTURING INDUSTRY IN EGYPT - Negmeldin, Mohamed Abdelkhalek Attia; Heshmat, Mahmoud; Eltawil, Amr (The South African Journal of Industrial Engineering, 2021)
In this paper, a system dynamics approach is introduced for the macro- planning of the selection of new product families in the consumer electronics industry in developing countries. A decision methodology structure is built that includes the impact factors of rapid technology changes and uncertainty. System dynamics models are designed to select the product family’s planning strategy, considering the different variables in marketing, product design, supply chain, and manufacturing method. The developed model is validated for a real case study of television manufacturing in Egypt. The results reveal that using system dynamics reflects the dynamics of the consumer electronics industry and can be used for its strategic planning.